IMPLEMENTING INDONESIAN LANGUAGE CHATBOT FOR ECOMMERCE SITE USING ARTIFICIAL INTELLIGENCE MARKUP LANGUAGE (AIML) - Stefanus Ardhito Prasetya; Alva Erwin; Maulahikmah Galinium (Prosiding Seminar Nasional Pakar, 2018)
E-Commerce becomes one of the hits in the online world nowadays. Peopleare tending to buy things online. Some e-commerce sites providechatting withtheir contact person to get in touch with their customers every time. However,there is another alternative to get in touch with the customers, which is usingChatbot. It can be used for 24 hours every day as long as the server is on. It canhelp customers to know more about the products. Furthermore, customers getinformation that being asked. This Chatbot is built using Artificial IntelligenceMarkup Language (AIML) and Pandorabots as the interpreter. This researchaims to found right AIML interpreter which can be used in Indonesianlanguage E-Commerce website. By holding experiment with respondent, itsaccuracy is measured. The result shows that the Chatbot still needsimprovement. Chatbot knowledge pattern matching rules should be enrichedbased on the questions that customers input in order to construct rules.